Robert C. Ogden papers - Ogden, Robert C. (Robert Curtis), 1836-1913.; Mitchell, Samuel Chiles, 1864-1948.
Correspondence, memoranda, speeches, writings, reports, family papers, printed matter, and other papers relating primarily to Ogden's business career, interests in philanthropy and religion, and activities on behalf of education of African Americans in the South. Documents his involvement with the Conference on Education in the South; General Education Board (New York, N.Y.); Hampton Institute; Presbyterian church in Philadelphia, Pa., and New York, N.Y.; Southern Education Board; Southern Improvement Company (1900-1918), an effort to facilitate African-American land ownership in the South; Tuskegee Institute; Union Theological Seminary (New York, N.Y.); and various philanthropies and disaster relief efforts. Includes an unpublished biography of Ogden by Samuel Chiles Mitchell, along with notes and copies of letters collected by Mitchell. Family papers include correspondence of Ogden's daughter, Helen Ogden Purves, and her husband, Alexander Purves. Other correspondents include Lyman Abbott, Edwin Anderson Alderman, S.C. Armstrong, Charles B. Aycock, Ray Stannard Baker, William Henry Baldwin, Edward William Bok, Nicholas Murray Butler, Wallace Buttrick, Andrew Carnegie, Frank R. Chambers, P.P. Claxton, Schuyler Colfax, J.L.M. Curry, Charles William Dabney, W.E.B. Du Bois, Hollis Burke Frissell, Frederick Taylor Gates, Job E. Hedges, David Franklin Houston, Seaman Ashahel Knapp, Seth Low, Charles Duncan McIver, Samuel Chiles Mitchell, Walter Hines Page, George Foster Peabody, John D. Rockefeller, Theodore Roosevelt, William Jay Schieffelin, Albert Shaw, William H. Taft, Oswald Garrison Villard, John Wanamaker, Booker T. Washington, and Woodrow Wilson.
Businessman and philanthropist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Index to selected correspondents in the Special Correspondence series available in the Library of Congress Manuscript Reading Room and at http://www.loc.gov/rr/mss/f-aids/ms012139.appx.pdf
Keywords: Abbott, Lyman, -- 1835-1922 -- Correspondence; Alderman, Edwin Anderson, -- 1861-1931 -- Correspondence; Armstrong, S. C. -- 1839-1893 -- Correspondence; Aycock, Charles B. -- 1859-1912 -- Correspondence; Baker, Ray Stannard, -- 1870-1946 -- Correspondence; Baldwin, William Henry, -- 1863-1905 -- Correspondence; Bok, Edward William, -- 1863-1930 -- Correspondence; Butler, Nicholas Murray, -- 1862-1947 -- Correspondence; Buttrick, Wallace, -- 1853-1926 -- Correspondence; Carnegie, Andrew, -- 1835-1919 -- Correspondence; Chambers, Frank R. -- Correspondence; Claxton, P. P. -- 1862-1957 -- Correspondence; Colfax, Schuyler, -- 1823-1885 -- Correspondence; Curry, J. L. M. -- 1825-1903 -- Correspondence; Dabney, Charles William, -- 1855-1945 -- Correspondence; Du Bois, W. E. B. -- 1868-1963 -- Correspondence; Frissell, Hollis Burke, -- 1851-1917 -- Correspondence; Gates, Frederick Taylor, -- 1853-1929 -- Correspondence; Hedges, Job E. -- 1862-1925 -- Correspondence; Houston, David Franklin, -- 1866-1940 -- Correspondence; Knapp, Seaman Ashahel, -- 1833-1911 -- Correspondence; Low, Seth, -- 1850-1916 -- Correspondence; McIver, Charles Duncan, -- 1860-1906Seaman Ashahel; Mitchell, Samuel Chiles, -- 1864-1948 -- Correspondence; Page, Walter Hines, -- 1855-1918 -- Correspondence; Peabody, George Foster, -- 1852-1938 -- Correspondence; Purves, Alexander, -- -1905 -- Correspondence; Purves, Helen Ogden -- Correspondence; Rockefeller, John D. -- 1839-1937 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Schieffelin, William Jay, -- 1866- -- Correspondence; Shaw, Albert, -- 1857-1947 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Villard, Oswald Garrison, -- 1872-1949 -- Correspondence; Wanamaker, John, -- 1838-1922 -- Correspondence; Washington, Booker T., -- 1856-1915 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Ogden family; Conference on Education in the South; General Education Board (New York, N.Y.); Hampton Institute; Tuskegee Institute; Southern Improvement Company (1900-1918); Union Theological Seminary (New York, N.Y.); African Americans -- Education; African Americans -- Southern States; Disaster relief; Education -- Southern States; Land tenure -- Southern States; Humanitarianism; Presbyterian Church -- Pennsylvania -- Philadelphia; Presbyterian Church -- New York (State) -- New York; Religion; Businessmen; Philanthropists